PENGARUH DISIPLIN KERJA, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA CV.MUSA’ADAH P2S2 DI KABUPATEN SITUBONDO - Kuni Afifah; Lusiana Tulhusnah; Hendra Syahputra (Fakultas Ekonomi dan Bisnis, 2025)
Human resource management is a branch of management that focuses on managing human elements. In an organization, humans are considered the main asset because their role is very important in achieving predetermined goals. The effectiveness of human resource utilization is the main indicator in assessing the success of management in an organization. CV.Musa'adah P2S2 (Pondok Pesantren Salafiyah Syafi'iyah) is a company that produces packaged drinking water (AMDK). The AMDK produced is named Syifa P2S2 drinking water CV. Musa'adah P2S2 has several goals to increase production and quality in its mineral water products. To fulfill a company's goals, of course CV.Musa'adah P2S2 must be able to manage human resources well and with quality. To achieve optimal work results, employees are entitled to get results from work in the form of compensation from the company. The purpose of this study is to analyze and test the Effect of Work Discipline, Compensation and Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable at CV. Musa'adah P2S2 in Situbondo Regency. This research is a quantitative study. The population used in this study was 75 employees. The sampling technique used simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Method - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, showed that Work Discipline has a positive and significant effect on Job Satisfaction, Compensation has a positive and significant effect on Job Satisfaction, Work Environment has a positive and significant effect on Job Satisfaction, Work Discipline has a positive and significant effect on Employee Performance, Compensation has a positive and significant effect on Employee Performance, Work Environment has a positive and significant effect on Employee Performance, Consumer satisfaction has a positive and significant effect on Employee Performance. The results of the indirect influence hypothesis test show that the variable Work discipline on employee performance through Job satisfaction has a positive and significant effect, Compensation on employee performance through Job satisfaction has a positive and significant effect, Work environment on employee performance through Job satisfaction has a positive and significant effect.